Inspiring green consumer choices : leverage neuroscience to reshape marketplace behavior - Smith, Michael Eugene (New Yort : Kogan Page, 2021)
'While many consumers profess a desire to help end climate change by engaging in more sustainable behaviors, consumer behavior experts note the'say-do' gap between expressed intention and behavior. How do we explain this? What, if anything, can consumers be encouraged to do to close this gap and purchase sustainable products and services? Inspiring Green Consumer Choices explains the factors that underlie the discrepancy between consumers' expressed preferences and their incongruous behavior in the marketplace. Drawing from advances in neuroscience, behavioral economics and experimental psychology, the author reveals how marketplace behavior is not always rational. Instead it is frequently the product of mental shortcuts, triggered by situational cues and colored by implicit emotional responses. In making purchasing decisions, routine consumer behavior is governed less by intention than by mental habits and unconscious response biases.These tendencies are difficult (but not impossible) to change. Inspiring Green Consumer Choices outlines how techniques such as psychological framing, design of choice architectures and pricing strategy can be used to disrupt habits and promote sustainable behavior. The author also addresses the role that legislative policy and changing social norms can play in accelerating and sustaining behavior change. Illustrated with case studies and filled with best practices, Inspiring Green Consumer Choices helps marketers understand how consumers make purchase decisions in order to shift consumption choices towards a more sustainable future'--
Includes bibliographical references and index.
Keywords: Consumer behavior -- Psychological aspects; Product design -- Psychological aspects; Choice (Psychology).; Marketing